1995
DOI: 10.1017/s0967199400002707
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic sperm injection in dysmorphic human oocytes

Abstract: SummaryFertilisation and development of dysmorphic human oocytes recovered from hyperstimulated ovaries have been evaluated following intracytoplasmic sperm injection (ICSI) for treatment of male infertility. A total of 2968 oocytes at metaphase II of meiosis were injected, of which 806 (27.2%) were dysmorphic at the light microscopic level. Cytoplasmic abnormalities included granularity, areas of necrosis, organelle clustering, vacuoles, and accumulating saccules of smooth endoplasmic reticulum. Anomalies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 14 publications
1
41
2
1
Order By: Relevance
“…In this work the author describes a similar frequency of aneuploidies in oocytes with granules in comparison with oocytes with normal appearance. For Alikani et al [27] the most commonly encountered cytoplasmic anomaly was partial intracellular necrosis, evidenced by the presence of several small scattered dense bodies (presumably chromatin) or pyknotic nuclei and the majority of such oocytes were normally fertilized.…”
Section: Discussionmentioning
confidence: 99%
“…In this work the author describes a similar frequency of aneuploidies in oocytes with granules in comparison with oocytes with normal appearance. For Alikani et al [27] the most commonly encountered cytoplasmic anomaly was partial intracellular necrosis, evidenced by the presence of several small scattered dense bodies (presumably chromatin) or pyknotic nuclei and the majority of such oocytes were normally fertilized.…”
Section: Discussionmentioning
confidence: 99%
“…Many other parameters have also been analysed in oocytes such as zona pellucida thickness, spindle birefringence and extracellular dysmorphisms [36,47,48]. Results vary as to whether distinct oocyte dysmorphisms have any relation to fertilisation and development rates, probably due to a discordance in the scoring of these dysmorphisms [50], although an effect on pregnancies is often noted [21,36,47,50].…”
Section: Introductionmentioning
confidence: 99%
“…or extra-cytoplasmic dysmorphisms (increased peri-vitellin space, fragmented polar body, granular zona pellucida…) [2,3]. Since several years, it was suggested that oocyte morphology could influence success rates in assisted procreation [1,[4][5][6]. However, the variety of dysmorphisms and the studied consequences as well as the variety of experimental models and contradictory results did not allow drawing precise conclusions on the global impact of these dysmorphisms on pregnancy outcomes [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the variety of dysmorphisms and the studied consequences as well as the variety of experimental models and contradictory results did not allow drawing precise conclusions on the global impact of these dysmorphisms on pregnancy outcomes [7]. Moreover, most studies did not focus on the impact of an individual anomaly on IVF outcomes [1,[4][5][6]. SERa, on the other hand, have been studied independently by several groups and a negative effect of the SERa dysmorphism in terms of fertilization, embryo quality, implantation, pregnancy rates or perinatal complications has indeed been reported [8].…”
Section: Introductionmentioning
confidence: 99%